COMPARATIVE ANALYSIS OF THE RATIONAL-MATERIALISTIC APPROACH IN THE DEVELOPMENT OF PROFESSIONAL ETHICS OF A LAWYER - Luiza Djurayevna Tuganova (Western European Studies, 2024)
In our opinion, this article highlights some interesting aspects of the ideas of a professional approach in legal ethics. Of course, the article is mainly for informational purposes and does not pretend to fully cover and solve all problems in this area. One of our main goals is to draw attention to the need for further theoretical research and practical solutions in this area. The article also discusses such topical issues as the comparison of the rational and materialistic approach of professional ethics of a lawyer
Keywords: Law; Ethics; Cognitive Process; morality